Socio‐economic evaluation of human–dog coexistence: A 40,000 years history - Mohammad Fallahi; Ali Akbar Masoudi; Rasoul Vaez Torshizi; Ali Maghsoudi (Veterinary Medicine and Science)
Abstract The human–animal relationship and its benefits have been a popular issue in recent decades. This study focuses on the dog as a paradigmatic example of this complex bond. The relationship between human and dog evolved over thousands of years through the domestication process. During this period, climatic, cultural, geographical and social changes have had a direct impact on this bond. Dogs have a remarkable capacity to play a variety of roles that mirror the evolution of human societies. Subsequently, questions arise regarding the important and symbolic roles that canines played in ancient cultures, religions and mythological traditions. Specifically, how have these roles changed through history? This research aimed to explore the socio‐economic aspects of the human–dog relationship, spanning from ancient civilizations to modern societies. Through a systematic search methodology, this investigation seeks to provide insights into the dynamics of the complex human–dog relationship, including historical backgrounds, socio‐cultural dynamics, economic implications and associated challenges. Additionally, the present study addresses the environmental concerns that emerge alongside rising stray dog populations. This research emphasizes the importance of strategies to balance the benefits of this coexistence that promote human and animal welfare.